Uncovering deep mysteries: The underwater life of an amphibious louse - Leonardi, María Soledad; Lazzari, Claudio Ricardo (Journal of Insect Physiology)
Despite the incredible success of insects in colonizing almost every habitat, they remain virtually absent in one major environment – the open sea. A variety of hypotheses have been raised to explain why just a few insect species are present in the ocean, but none of them appears to be fully explanatory. Lice belonging to the family Echinophthiriidae are ectoparasites on different species of pinnipeds and river otters, i.e. they have amphibious hosts, who regularly perform long excursions into the open sea reaching depths of hundreds of meters (thousands of feets). Consequently, lice must be able to support not only changes in their surrounding media, but also extreme variations in hydrostatic pressure as well as breathing in a low oxygen atmosphere. In order to shed some light on the way lice can survive during the diving excursions of their hosts, we have performed a series of experiments to test the survival capability of different instars of Antarctophthirus microchir (Phthiraptera: Anoplura) from South American sea lions Otaria flavescens, when submerged into seawater. These experiments were aimed at analyzing: (a) immersion tolerance along the louse life; (b) lice’s ability to obtain oxygen from seawater; (c) physiological responses and mechanisms involved in survival underwater. Our experiments showed that the forms present in nondiving pups – i.e. eggs and first-instar nymphs – were unable to tolerate immersion in water, while fol- lowing instars and adults, all usually found in diving hosts, supported it very well. Furthermore, as long as the level of oxygen dissolved in water was higher, the lice survival capability underwater increased, and the recovery period after returning to air declined. These results are discussed in relation to host ecology, host exploitation and lice functional morphology. Fil: Leonardi, María Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Lazzari, Claudio Ricardo. ...